Remote Mesoscopic Signatures of Induced Magnetic Texture in Graphene - N. Arabchigavkani; R. Somphonsane; H. Ramamoorthy; G. He; J. Nathawat; S. Yin; B. Barut; K. He; M._D. Randle; R. Dixit; K. Sakanashi; N. Aoki; et al. (My University, 2021)
Mesoscopic conductance fluctuations are a ubiquitous signature of phase-coherent transport in small conductors, exhibiting universal character independent of system details. In this work, however, we demonstrate a pronounced breakdown of this universality, due to the interplay of local and remote phenomena in transport. Our experiments are performed in a graphene-based interaction-detection geometry, in which an artificial magnetic texture is induced in the graphene layer by covering a portion of it with a micromagnet. When probing conduction at some distance from this region, the strong influence of remote factors is manifested through the appearance of giant conductance fluctuations, with amplitude much larger than $e^2/h$. This violation of one of the fundamental tenets of mesoscopic physics dramatically demonstrates how local considerations can be overwhelmed by remote signatures in phase-coherent conductors
Keywords: Mesoscopic physics; Weak localization; Texture (cosmology); Graphene research and applications